2019
DOI: 10.1111/myc.12886
|View full text |Cite
|
Sign up to set email alerts
|

Candida auris otomycosis in Iran and review of recent literature

Abstract: Summary Candida auris is a multidrug‐resistant yeast emerging in immunocompromised and in otherwise healthy individuals. Due to difficulties in microbiological identification of C. auris because of the lack of available laboratory technology in developing countries, the number of patients affected is most likely underestimated. We report the first case of C. auris otitis which now adds Iran as the fifth country around the Persian Gulf, in addition to Kuwait, Oman, United Arab Emirates and Saudi Arabia. Candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 31 publications
3
92
2
1
Order By: Relevance
“…For the STR analysis 444 C. auris isolates from Austria(27), Belgium(28), Colombia (hospitals in Barranquilla, Bogota, Cartagena, Medellin, Popayan and Santa Maria), India(29), Iran(30), Japan(29), Korea(29), Kuwait(31), Oman(32), Pakistan(17), Russia(33), South-Africa(29), Spain(26), The Netherlands(34), United Kingdom(35) and Venezuela(6) were used. For a complete overview of isolates see Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…For the STR analysis 444 C. auris isolates from Austria(27), Belgium(28), Colombia (hospitals in Barranquilla, Bogota, Cartagena, Medellin, Popayan and Santa Maria), India(29), Iran(30), Japan(29), Korea(29), Kuwait(31), Oman(32), Pakistan(17), Russia(33), South-Africa(29), Spain(26), The Netherlands(34), United Kingdom(35) and Venezuela(6) were used. For a complete overview of isolates see Supplementary Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, C. sequences. Recently, a fifth clade of C. auris was identified from a patient in Iran who never travelled outside that country (17). The WGS revealed that the Iran C. auris isolate was >200,000 SNPs apart from the other four clades (18).…”
Section: Downloaded Frommentioning
confidence: 99%
“…These populations were grouped into South Asian (I), East Asian (II), African (III), and South American (IV) clades. Recently, a fifth clade of C. auris was identified from a patient in Iran who never travelled outside that country (17). The WGS revealed that the Iran C. auris isolate was genetically distinct and separated by >200, 000 single nucleotide polymorphisms (SNPs) from the other four known C. auris clades (18).…”
Section: Introductionmentioning
confidence: 99%
“…The Korean collection used in the present study showed that since the first three reported cases of C. auris fungemia (1), only one patient isolate from blood cultures was obtained in 2017. The isolation of this organism from ear cultures has been observed continually from several hospitals in Korea (11,24). To date, no genotyping of the blood isolates of C. auris from the first three cases of fungemia in Korea has been reported.…”
Section: Figmentioning
confidence: 99%